Proceedings of the 13th Workshop on Privacy in the Electronic Society 2014
DOI: 10.1145/2665943.2665963
|View full text |Cite
|
Sign up to set email alerts
|

What Deters Jane from Preventing Identification and Tracking on the Web?

Abstract: Recent revelations about surveillance by several institutions and de-identification can be expected to have increased public awareness of identification-and tracking-related privacy threats. It is reasonable to expect that the general public has started using corresponding privacy protection mechanisms. Our goal with this research was to determine whether they actually do this. If not, we wanted to explore possible explanations for not uptaken such privacy-protecting countermeasures. We interviewed 20 (mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 24 publications
6
27
1
Order By: Relevance
“…Studies by McDonald et al [11], [12], in form of interviews and online surveys, further revealed lack of awareness and misconceptions prevalent among the users regarding cookies. Shirazi et al furthermore revealed a number of misconceptions, including lack of awareness and feeling of resignation, regarding web tracking and countermeasures against it in their interviews [16]. Similarly, the prevalence of misconceptions regarding cookies and online trackings emerged from the study by Ur et al [18] conducted in the form of interviews.…”
Section: Related Workmentioning
confidence: 99%
“…Studies by McDonald et al [11], [12], in form of interviews and online surveys, further revealed lack of awareness and misconceptions prevalent among the users regarding cookies. Shirazi et al furthermore revealed a number of misconceptions, including lack of awareness and feeling of resignation, regarding web tracking and countermeasures against it in their interviews [16]. Similarly, the prevalence of misconceptions regarding cookies and online trackings emerged from the study by Ur et al [18] conducted in the form of interviews.…”
Section: Related Workmentioning
confidence: 99%
“…Other examples of assessing people's awareness of privacy risks are interviews conducted by Friedman et al [24], who found that people were concerned about risks to their information and especially their privacy, but did not further specify these privacy risks, a survey on security and privacy risks of eHealth wearables [25], interviews combined with a field study concerning the risks of WiFi use [26], a comprehensive study on user regrets regarding Facebook posts [27], a survey assessing perceived risks of using mobile devices to conduct online transactions [28], and surveys and interviews concerning risks of cloud storage [29]. Shirazi and Volkamer [30] conducted interviews with 20 people on identification and tracking on the web, and found that their participants most often mentioned personalized advertising as a possible consequence, which some of them even considered to be beneficial. Melicher et al [31] found that participants in their interview study were less comfortable with hidden outcomes of online tracking (e.g., price discrimination) than with more overt consequences (e.g., targeted advertisement).…”
Section: A Mental Models Of Privacy Consequencesmentioning
confidence: 99%
“…A few qualitative studies have been conducted on what obstacles users face when aiming to protect their privacy in several contexts. Shirazi and Volkamer [30], for example, conducted interviews with 20 people, most of them lay users, to investigate why most people do not use tools to protect themselves against identification and tracking on the web. They identified seven different explanations: (1) people mainly worry about privacy issues other than identification and tracking, (2) people are not aware of the assessment of meta-data, (3) people are not aware of the possibility to use meta-data for identification and tracking, (4) people are not concerned because of several misconceptions such as being not aware of consequences or the feeling that they have nothing to hide, (5) people are not aware of protection tools, (6) people are not able to use protection tools properly, (7) people become side-tracked.…”
Section: B Obstacles For Privacy Protectionmentioning
confidence: 99%
“…As such, many of them indicated that the users tend to misunderstand the function of cookies and their effect on privacy [2], [5], [6], [10], [11]. Other findings focused on countermeasures against web tracking via cookies, determining the lack of usability and understandability of tools that enable users to control their cookie settings, including standard browser settings [3], [8], and general lack of awareness among users regarding the existence of such tools [6], [15], [16].…”
Section: Related Workmentioning
confidence: 99%
“…These findings are also reflected in other studies on cookie settings from the user perspective. These show that users often lack understanding regarding the purpose of cookies and their effect on users' privacy [2] and that existing interfaces for cookie settings often use language that is too technical or they are otherwise confusing the users [15].…”
Section: Introductionmentioning
confidence: 99%